2020
DOI: 10.1111/echo.14716
|View full text |Cite
|
Sign up to set email alerts
|

Presence and prognostic value of ventricular diastolic function in arrhythmogenic right ventricular cardiomyopathy

Abstract: Introduction Limited data exist regarding the presence and importance of diastolic parameters in patients with arrhythmogenic right ventricular cardiomyopathy (ARVC). We sought to evaluate RV diastolic parameters and echo‐based diastolic predictors of major adverse cardiovascular events (MACE). Method 48 patients with a definitive diagnosis of ARVC were included and followed for 6‐18 months. A comprehensive standard two‐dimensional (2D) transthoracic echocardiography (TTE) with precise evaluation of systolic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Despite high RV and RVOT flow velocities, athletes had lower MKE values both along the whole RV and more specifically in the RVOT regions during both systole and diastole compared to ARVC patients. This finding likely reflects the differences in RV compliance, which is higher in athletes, whereas ARVC patients can develop RV diastolic dysfunction, which imply a negative prognosis 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite high RV and RVOT flow velocities, athletes had lower MKE values both along the whole RV and more specifically in the RVOT regions during both systole and diastole compared to ARVC patients. This finding likely reflects the differences in RV compliance, which is higher in athletes, whereas ARVC patients can develop RV diastolic dysfunction, which imply a negative prognosis 18 .…”
Section: Discussionmentioning
confidence: 99%
“…It is quite surprising that the other side of the story (RV pathology leading to LV diastolic dysfunction) remains grossly untold. In this special issue, however, Sadeghpour et al 12 have shown that in subjects with arrhythmogenic right ventricular cardiomyopathy, left ventricular diastolic dysfunction could be present.…”
Section: The Right Ventricle and The Mitral Valve: Diastology Is Ubiqmentioning
confidence: 98%
“…RA area, LA volume index, RVOT diameter and TAPSE were associated with increased odds of having atrial arrhythmias, even after adjusting for age 13 . In 48 patients with ACM followed for 6-18 months, e' of the tricuspid valve annulus, peak E velocity of the mitral valve, septal e' at the mitral valve, RA area and volume, alongside with right ventricular myocardial performance index were strong predictors for major adverse cardiac events 14 . Moreover, among 64 patients with ACM defi ned by imaging criteria (echocardiography and CMR), as well as genetic testing, lower RV EF and LV EF values were predictive for biventricular involvement.…”
mentioning
confidence: 96%